Mana Wahine: Māori Women in Music - Sheehan, Maree (Te Kaharoa, 2016)
Moana Maniapoto and Hinewehi Mohi are famous for having pioneered a distinctively Māori form of popular and political music in the 1990s, and they continue to produce remarkable contemporary waiata for audiences in Aotearoa and overseas. Their successes have inspired other artists, and more importantly, they have both made significant contributions to the empowerment and strengthening of te reo Māori and mātaranga Māori. Recognising what has happened since the 1990s, this paper takes a constructive look at the current state of Māori music and considers how to produce a new wave of creativity for the 21st century for new generations of Māori and Indigenous composers, audiences and performers. How does popular music performance make a powerful contribution to the revitalisation of te reo Māori and mātauranga Māori? Maree Sheehan will lead a conversation with Moana Maniapoto and Hinewehi Mohi to discuss the lasting significance of their work for Māori music and culture, twenty-five years later.